Genome-wide association study of gastric adenocarcinoma in Asia: a comparison of associations between cardia and non-cardia tumours. Issue 10 (30th June 2015) - Hu, Nan; Wang, Zhaoming; Song, Xin; Wei, Lixuan; Kim, Byung Sik; Freedman, Neal D; Baek, Jiwon; Burdette, Laurie; Chang, Jiang; Chung, Charles; Dawsey, Sanford M; Ding, Ti; et al.
Abstract : Objective: Genome-wide association studies (GWAS) of gastric cancer have reported differences in single-nucleotide polymorphism (SNP) associations for tumour subtypes, particularly when divided by location into the gastric cardia versus the non-cardia. Design: Here we present results for a GWAS using 2350 East Asian gastric cancer cases divided as 1189 gastric cardia and 1027 gastric non-cardia cases and 2708 controls. We also included up to 3042 cardia cases, 4359 non-cardia cases and 7548 controls for replication from two Chinese studies and one Korean study. From the GWAS, we selected 12 top SNPs for each gastric cancer subtype, 4 top SNPs for total gastric cancer and 1 SNP in MUC1 for replication testing. Results: We observed genome-wide significant associations for rs10074991 in PRKAA1 at 5p13.1 for cardia (p=7.36×10 −12 ) and non-cardia cancers (p=2.42×10 −23 ) with per allele OR (95% CI) for the combined endpoint of 0.80 (0.77 to 0.83). At 6p21.1, rs2294693 near UNC5CL was significantly associated with gastric non-cardia cancer risk (p=2.50×10 −8 ), with OR (95% CI) of 1.18 (1.12 to 1.26), but there was only a nominal association for cardia cancer (p=1.47×10 −2 ). We also confirmed a previously reported association for rs4072037 in MUC1 with p=6.59×10 −8 for total gastric cancer and similar estimates for cardia and non-cardia cancers. Three SNPs in PSCA previously reported to be associated with gastric non-cardia cancer showed no apparent association for cardia cancer. Conclusions: Our results suggest that associations for SNPs with gastric cancer show some different results by tumour location in the stomach.